Nanoparticle-electrode collision processes: Investigating the contact time required for the diffusion-controlled monolayer underpotential deposition on impacting nanoparticles - Cutress, I; Rees, N; Zhou, Y; Compton, R (2011)
Recent work on faradaic processes occurring during thermal nanoparticle-electrode collisions contrasts significantly from analogous research using ultrasonically-driven microparticles, where no faradaic signals were found. It is suggested that this might be explained by the differences in both particle size and contact time. To investigate this, we present results from adapted Monte Carlo random walk simulations. Using the underpotential deposition of thallium onto silver nanoparticles as a model system, it is found that an estimated minimum contact time of ca. 10-4 s is required to deposit a complete monolayer (from a 10 mM solution) onto a nanoparticle of radius 45 nm. © 2011 Elsevier B.V. All rights reserved.